KARAKTERISTIK DAN GAMBARAN KLINIS PASIEN KANKER PAYUDARA YANG DIRAWAT INAP DI RSUD DR H CHASAN BOESOIRIE TERNATE TAHUN 2019 - Nurhasanah B Kasuba; Arif Santosa; fera the (Fakultas Kedokteran, Universitas Khairun, 2020)
Background : Breast cancer is caused by abnormal growth of mammary cells. The data released by Globocan (IARC) in 2018 reported 18.1 millions of new cancer cases emerged with a mortality rate of 9.6 millions. Out of this number, the percentage of breast cancer prevalence reached 11.6 with 6.6% mortality rate. A research conducted by Laisla 2017 in RSUP Haji Adam Malik Medan revealed that most breast cancer cases occurred to patients aged between 50-59 years old. Most patients were brought to the hospital when their cancers already reached advanced stages. Regarding this matter, this research was conducted to investigate the characteristics and clinical review of breast cancer inpatients in RSUD Dr. H. Chasan Boesoririe Ternate in 2019. Method : This descriptive research was conducted using the cross sectional research design. Research population and samples included new inpatients with breast cancer in RSUD Dr. H. CHasan Boesoririe Ternate whose medical records were complete and recorded from October – December 2019. Total sampling technique was employed to select 21 inpatients with breast cancer based on the predetermined inclusion and exclusion criteria. Outcome : Out of 21 patients with breast cancer, 43% were between 45-55 years old, elementary school graduates, married, and had some clinical symptoms including nipple retraction, peau d’orange, dimpling ulceration, erythema, firm lump on the skin (28.6%), at the stage III B cancer and most of their histopathology showed invasive ductal carcinomas. Key words : age, breast cancer, clinical review, education, marital status